2013
DOI: 10.1073/pnas.1317052110
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and biochemical analyses identify a family of chlorhexidine efflux proteins

Abstract: Significance Drug resistance is an increasing problem in clinical settings with some bacterial pathogens now resistant to virtually all available drugs. Chlorhexidine is a commonly used antiseptic and disinfectant in hospital environments, and there is increasing resistance to chlorhexidine seen in some pathogenic bacteria, such as Acinetobacter baumannii . This paper examines the global gene expression of A. baumannii in response to chlorh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
209
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(225 citation statements)
references
References 33 publications
13
209
0
3
Order By: Relevance
“…The copresence of the Tet(A) pump and Tet(M) for ribosomal protection was also noted (16). Lastly, a new type of efflux pump, AceI, was found to mediate resistance to chlorhexidine (563). Chlorhexidine itself also induces the expression of AceI and AdeABC.…”
Section: Acinetobacter Sppmentioning
confidence: 89%
See 1 more Smart Citation
“…The copresence of the Tet(A) pump and Tet(M) for ribosomal protection was also noted (16). Lastly, a new type of efflux pump, AceI, was found to mediate resistance to chlorhexidine (563). Chlorhexidine itself also induces the expression of AceI and AdeABC.…”
Section: Acinetobacter Sppmentioning
confidence: 89%
“…Chlorhexidine itself also induces the expression of AceI and AdeABC. AceI belongs to the bacterial transmembrane pair family and is grouped as a prototype member of the proteobacterial chlorhexidine efflux family (563). Similarly, the exposure of Acinetobacter baylyi to chlorhexidine also induced resistance to chlorhexidine and oxidants (564), which could potentially be attributed to efflux pumps.…”
Section: Acinetobacter Sppmentioning
confidence: 99%
“…Other highly upregulated genes include predicted metal transport systems and a predicted ABC transport system of unknown function that appears to be encoded by a mobile genetic element. The specific roles of these transport systems in the H-CHG stress response remain to be determined; possibilities include chlorhexidine efflux (note that a new family of chlorhexidine efflux proteins was recently identified for Gram-negative bacteria [67,68]), transport of metals to maintain redox balance in the cell, or transport of cell wall-related metabolites. Future studies will compare the transcriptomic response of E. faecium to H-CHG to that for CHG and sodium gluconate, which will help to determine which specific components of H-CHG are responsible for the transcriptional changes observed.…”
Section: Discussionmentioning
confidence: 99%
“…22,24 Previous studies on the in vitro activity of chlorhexidine against various bacteria found that the minimum inhibitory concentration of chlorhexidine for P. aeruginosa (5-60 µg/mL) was higher than that for S. aureus (0.5-1 µg/mL) and chlorhexidine-resistant A. baumannii and E. coli owing to a drug efflux pump. 25,26 In subgroup analyses, MDR bacterial colonization at enrollment had significantly fewer favorable events compared with no-MDR bacterial colonization at enrollment, and the MDR bacterial colonization was the major risk factor of unfavorable outcomes. The reason might be that MDR gram-negative bacteria isolated from the ICU patients in this study were resistant to chlorhexidine.…”
Section: Discussionmentioning
confidence: 99%